(untitled) (Research, Society and Development, 2022)
The initial training of teachers in the context of remote education has undergone several changes never seen in the globalized world. Thus, the supervised internship had to follow the process, as the initial training needed to continue. This work aims to propose a reflection on the construction of the teaching curriculum bases proposed by MEC and observe its contextualization according to the reality faced by 2nd year high school students at the Monte Santo State Elementary School, Campina Grande, Paraíba, in remote learning. The adopted methodology has a qualitative approach, of the case study type. From the results obtained, it was found that the supervised internship in remote education required the student to know new methodological resources to develop didactic-pedagogical strategies in remote classes. Despite all the efforts and debates throughout the curricular component, the interactions in the 2nd year class were only through asynchronous moments, which it was not possible to actually know the students. So, it is clear that despite its importance, the moment of pandemic greatly restricted the contact with the school and even with the target group of the internship, due to the lack of synchronous moments in this case.